2016
DOI: 10.1017/s0022215116008331
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum thyroglobulin levels at the time of ablative radioactive iodine therapy indicate a worse prognosis in thyroid cancer: an Australian retrospective cohort study

Abstract: An elevated thyroglobulin level of 27.5 µg/l or higher at the time of ablative radioactive iodine therapy is a prognostic indicator for macroscopic disease recurrence in well-differentiated thyroid carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…Matthews et al . described patients with a thyroglobulin level of 27.5 μg/l or higher with reduced disease-free survival [18]. Similarly, Podnos et al .…”
Section: Discussionmentioning
confidence: 99%
“…Matthews et al . described patients with a thyroglobulin level of 27.5 μg/l or higher with reduced disease-free survival [18]. Similarly, Podnos et al .…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Webb et al [5] including data from nearly 4,000 patients showed an overall NPV of pre-RAI sTg < 10 µg/L of 94.2% for predicting disease-free status. In a more recent Australian study by Matthews et al [4], a significant difference in prognosis was found in patients with elevated Tg values (> 27.5 µg/L) at the time of RAI administration. Conversely, our study could not confirm the role of serum pre-Tg as a risk factor for disease progression in patients considered to have persistent structural disease after initial therapy (group 2).…”
Section: Discussionmentioning
confidence: 89%
“…An accurate initial risk appraisal is therefore crucial in these patients because it not only defines the need for postoperative RAI administration, but also allows formulation of an appropriate surveillance strategy. Features known to correlate with poorer prognosis are higher American Joint Committee on Cancer (AJCC) stage, advanced age, male sex, extrathyroidal extension, and certain histological subtypes [4], but many authors have also researched serum Tg measured just before RAI administration as a marker for predicting persistent or recurrent disease, with reported cut-off values ranging from 1.0 to 10.0 µg/L [5][6][7][8]. Due to its high negative predictive value (NPV) in this setting, preablation Tg has been suggested to be a useful and inexpensive tool for risk evaluation early on during and after initial treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative serum thyroglobulin levels can be a predictor of persistent disease after surgery, according to the ATA's guidelines, but the optimal cutoff value to guide decisions in terms of appropriate radioiodine dose has not yet been well established. Several studies (11)(12)(13)(14)(15)(22)(23)(24)(25)(26)(30)(31)(32)(33)(34)(35)(36)(37) have demonstrated the clinical use of the serum thyroglobulin measurement (either TSH stimulated or non-stimulated) as a tool to aid in initial risk stratification to guide treatment and predict prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, some studies associate greater ps-Tg values with worse prognosis in DTC patients. In one prospective study, a ps-Tg threshold of >5 ng/mL was considered appropriate to indicate RIT ( 31 ). Two other studies ( 34 , 35 ) reported that elevated Tg levels (>5-6 ng/mL) may be a predictor of failing ablation, after administration of RIT doses of 30 mCi ( 34 ) and 100 mCi ( 35 ), suggesting that higher Tg levels could be correlated with a more aggressive tumor profile.…”
Section: Discussionmentioning
confidence: 99%